Brabbling Women : Disorderly Speech and the Law in Early Virginia - Snyder, Terri L., 1956- (Book collections on Project MUSE., 2003)
"Brabbling Women takes its title from a 1662 law enacted by Virginia's burgesses, which was intended to offer relief to the "poore husbands" forced into defamation suits because their "brabling" wives had slandered or scandalized their neighbors. To quell such episodes of female misrule, lawmakers decreed that husbands could choose either to pay damages or to have their wives publicly ducked." "But there was more at stake here. By examining women's use of language, Terri L. Snyder demonstrates how women resisted and challenged oppressive political, legal, and cultural practices in colonial Virginia. Contending that women's voices are heard most clearly during episodes of crisis, Snyder focuses on disorderly speech to illustrate women's complex relationships to law and authority in the seventeenth century."--Jacket.